Climate Change Communication and Transboundary Water Politics: A Comparative Media Framing Analysis of the Indus Water Treaty in Pakistan and India: https://doi.org/10.55966/assaj.2025.4.1.0122 - Syeda Sumblah Bukhari; Noor ul Ain Nasir; Shahab Ali; Sidra Aziz (`, 2025)
This paper examines the manner in which Pakistani and Indian media represent the Indus Water Treaty (IWT) in the bigger picture of climate change and transboundary water politics. The study will analyze the tone, thematic emphasis and narrative approaches of top newspapers in the two countries on times of increased levels of water-related tensions and extreme climate phenomena using comparative framing analysis. This research aims to reveal whether the media discourse serves to support cooperation or trigger the conflict discourse, and how the narrative of climate change is placed in such frames. The study will present the availability of perspectives contributing to the overall understanding of the impacts of media in shaping the public deliberation and perception of common natural resources in South Asia and it will do so through the integration of the vision of environmental communication, international relations studies and media studies. Keywords: Climate Change Communication, Transboundary Water Politics, Indus Water Treaty, Media Framing, Pakistan, India